Promoting Plant-Based Therapies for Chronic Kidney Disease - Muhammad Ali Khan MPharm; Andrew J Kassianos PhD; Wendy E Hoy MD; AHM Khurshid Alam PhD; Helen G Healy MD; Glenda C Gobe PhD (SAGE Publishing, 2022)
Chronic kidney disease (CKD) is debilitating, increasing in incidence worldwide, and a financial and social burden on health systems. Kidney failure, the final stage of CKD, is life-threatening if untreated with kidney replacement therapies. Current therapies using commercially-available drugs, such as angiotensin-converting enzyme inhibitors, angiotensin II receptor blockers and calcium channel blockers, generally only delay the progression of CKD. This review article focuses on effective alternative therapies to improve the prevention and treatment of CKD, using plants or plant extracts. Three mechanistic processes that are well-documented in CKD pathogenesis are inflammation, fibrosis, and oxidative stress. Many plants and their extracts are already known to ameliorate kidney dysfunction through antioxidant action, with subsequent benefits on inflammation and fibrosis. In vitro and in vivo experiments using plant-based therapies for pre-clinical research demonstrate some robust therapeutic benefits. In the CKD clinic, combination treatments of plant extracts with conventional therapies that are seen as relatively successful currently may confer additive or synergistic renoprotective effects. Therefore, the aim of recent research is to identify, rigorously test pre-clinically and clinically, and avoid any toxic outcomes to obtain optimal therapeutic benefit from medicinal plants. This review may prove to be a filtering tool to researchers into complementary and alternative medicines to find out the current trends of using plant-based therapies for the treatment of kidney diseases, including CKD.